2022
DOI: 10.3390/ani12192535
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cold Environments on Growth, Antioxidant Status, Immunity and Expression of Related Genes in Lambs

Abstract: Cold climates may be a risk to the health and welfare of lambs during winter because cold environments alter the physiological processes of lambs, and we used cold environments with three different temperature gradients—an indoor heating control group (IHC) using electric heating; an indoor temperature group (IT) with intermittent and slight degrees of stimulation of coldness; an outdoor temperature group (OT) exposed to cold environments in an external natural environment. The results showed that the lambs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that cold stress induces stress responses in ruminants, resulting in elevated concentrations of serum glucocorticoids, triiodothyronine, and thyroxine [ 39 ]. In our study, the RTW increased the concentrations of serum T3 and T4, which could contribute to the promotion of gluconeogenesis and hepatic glycogen synthesis, enhance thermogenesis, and improve the resistance of the organism to low-temperature environments [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that cold stress induces stress responses in ruminants, resulting in elevated concentrations of serum glucocorticoids, triiodothyronine, and thyroxine [ 39 ]. In our study, the RTW increased the concentrations of serum T3 and T4, which could contribute to the promotion of gluconeogenesis and hepatic glycogen synthesis, enhance thermogenesis, and improve the resistance of the organism to low-temperature environments [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…During colder periods, though, the temperature inside the sheep barn is lower than the lower critical temperature of the animals' TNZ. As a result, the animals consume more feed to retain their body temperature within their TNZ, and they face a change in their metabolic reactions [6,16], which leads to an increase in feed intake during the winter months [17][18][19] without leading to a weight increase [20]. As reported in the literature, an increase in feed intake leads to an increase in GHG emissions [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that hypothermia induced by cold stress can lead to hypoxia, hypoglycaemia, and metabolic acidosis in lambs [ 3 ]. Additionally, the cold environment affects the growth performance, antioxidant status, immune function and expression of related genes in lambs [ 4 ]. Based on the various adverse effects of cold stress on newborn goats, this study aims to explore the regulatory effect of cold exposure on hepatic metabolism in newborn goats.…”
Section: Introductionmentioning
confidence: 99%